2018
DOI: 10.1111/jace.16071
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of CeO2 nanoparticles with different morphologies and their properties as peroxidase mimic

Abstract: The overall objective of this work was to identify and determine the controlling factors of catalytic activity of CeO2 nanoparticles with different properties. Therefore, four kinds of CeO2 nanoparticles are successfully synthesized and used as peroxidase mimics. The results reveal that the catalytic activity is related to specific surface area and surface oxygen (Osur) content. For different CeO2 nanoparticles, specific surface area is the leading factor of catalytic activity. The catalytic activity increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…Nanoscale cerium oxide can be synthesized by precipitation method [36], hydrothermal method [37], combustion method, decomposition method, oxidation and wet synthesis method, solvothermal method, green/bio directed synthesis, sonochemical method [38], microwave assisted method, micro-emulsion method [39], sol-gel method [40], and so on. Different synthesis methods can produce nanoscale cerium oxide with different forms, shapes and sizes, such as nanoclusters, octahedrons, cube, and rod shapes, as shown in Figure 1 [41]. Different size and surface morphologies have different effects on its physical and chemical properties [42].…”
Section: Synthesis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoscale cerium oxide can be synthesized by precipitation method [36], hydrothermal method [37], combustion method, decomposition method, oxidation and wet synthesis method, solvothermal method, green/bio directed synthesis, sonochemical method [38], microwave assisted method, micro-emulsion method [39], sol-gel method [40], and so on. Different synthesis methods can produce nanoscale cerium oxide with different forms, shapes and sizes, such as nanoclusters, octahedrons, cube, and rod shapes, as shown in Figure 1 [41]. Different size and surface morphologies have different effects on its physical and chemical properties [42].…”
Section: Synthesis Methodsmentioning
confidence: 99%
“…Ce 4+ has catalase-like activity and can convert H 2 O 2 into O 2 and H + , changing the Ce 4+ valence state to Ce 3+ (with the corresponding changes in oxygen vacancies), and adopting the original CeO 2 NP state in phosphate buffers (pH 7.4) [52]. Baoliang Zhang and coworkers [41] found that nanoscale cerium oxide has mimicked the activity of superoxide dismutase and catalase because of its reversible switching ability from Ce 3+ [53] proposed a nanoscale cerium oxide model simulating the reaction mechanism of catalase, which is summarized as follows: Summing reactions ( 6) and ( 7) and ( 8) and ( 9) results in reaction ( 10)…”
Section: Catalasementioning
confidence: 99%
“…Nanozymes have attracted increasing attention in the past decades in the field of catalysis because of their fantastic advantages, including low cost, facile synthesis, excellent stability and are easy to manipulate in optical sensing [ 1 , 2 ]. After the Fe 3 O 4 nanoparticles was first reported as the peroxidaselike nanoenzyme to catalyze 3,3′,5,5′-tetramethylbenzidine (TMB) in the presence of H 2 O 2 to produce a blue color compound 3,3′,5,5′-tetramethylbenzidine diimine (TMBDI) [ 3 ], different kinds of nanozymes such as carbon based nanomaterials [ 4 ], metal nanoparticles [ 5 , 6 ], metal oxides [ 7 , 8 ] and metal oxide nanocomposites [ 9 , 10 ] have been discovered to replace natural enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…The heterogeneous Fenton system not only has the merits of the traditional Fenton method but also has an accelerated reaction speed, reduces the iron sludge, broadens the pH range, and minimizes the influence of iron ions on the chroma of water . Some heterogeneous materials have already been successfully fabricated, including Fe 2 O 3 ‐SiO 2 , goethite, Fe 2 O 3 /Bi 2 WO 6 , NdFeB magnetic activated carbon, and H 3 PW 12 O 40 supported Fe‐bentonite …”
Section: Introductionmentioning
confidence: 99%